Transjugular intrahepatic portosystemic shunt for portal vein thrombosis with variceal bleeding in liver cirrhosis: outcomes and predictors in a prospective cohort study. (28th August 2015) - Qi, Xingshun; He, Chuangye; Guo, Wengang; Yin, Zhanxin; Wang, Jianhong; Wang, Zhengyu; Niu, Jing; Bai, Ming; Yang, Zhiping; Fan, Daiming; Han, Guohong
Abstract: Background & Aims: The role of transjugular intrahepatic portosystemic shunt (TIPS) for the secondary prophylaxis of variceal bleeding in cirrhotic patients with portal vein thrombosis (PVT) remains obscure. This prospective cohort study aimed to assess the risk factors associated with TIPS technical success, outcome and prognosis in cirrhotic patients with PVT and a history of variceal bleeding. Methods: Between May 2009 and April 2011, 51 cirrhotic patients with PVT who attempted TIPS procedures for the prevention of variceal rebleeding were enrolled. Results: TIPS success rate was 84% (43/51). An increased degree of thrombosis within the portal trunk and portal vein branches was inversely associated with TIPS success. Median follow‐up time was 40.07 months (range: 0.02–56.87). The cumulative risk of rebleeding was significantly different between TIPS success and failure group ( P = 0.002). The univariate analysis also demonstrated that TIPS failure was the only significant predictor associated with rebleeding (hazard ratio [HR] = 4.174, 95% confidence interval [CI]: 1.558–11.186). In TIPS success group, the cumulative rates free of shunt dysfunction at the 6th and 12th month were 79% and 76% respectively. Absence of total superior mesenteric vein (SMV) thrombosis was the only independent predictor (HR = 0.189, 95% CI: 0.047–0.755). In TIPS success group, the 1‐ and 3‐year cumulative survival rates were 77% and 62% respectively. Albumin level was the only independent predictor (HR = 0.877, 95% CI: 0.779–0.986). Conclusion: Successful TIPS insertions could effectively prevent from rebleeding in cirrhotic patients with PVT and variceal bleeding. Degree of PVT and SMV thrombosis was associated with TIPS failure and shunt dysfunction respectively.